PENGARUH PROJECT BASED LEARNING (PJBL) MENGGUNAKAN MEDIA AUDIOVISUAL BERBASIS KEARIFAN LOKAL TERHADAP KETERAMPILAN MENULIS TEKS RESENSI SISWA KELAS VIII SMP NEGERI 3 BATANG ANAI KABUPATEN PADANG PARIAMAN - Shidqi, Nadiah Agmi; Farel Olva Zuve; Afnita; Vivi Indriyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low writing skills of review texts of eighth grade students of SMP Negeri 3 Batang Anai, especially in structuring texts, using linguistic rules, and applying Enhanced Spelling. One effort to overcome this problem is by implementing a Project Based Learning model assisted by audiovisual media based on local wisdom. This study aims to determine the effect of the Project Based Learning model assisted by audiovisual media based on local wisdom on the writing skills of eighth grade students of SMP Negeri 3 Batang Anai. This study uses a quantitative approach with an experimental method and a Posttest Only Control Group Design. The research population is all eighth grade students of SMP Negeri 3 Batang Anai, while the research sample consists of two classes, namely the experimental class consisting of 30 students and the control class consisting of 29 students. Data collection techniques are carried out through performance tests in the form of writing review texts. Data are analyzed through normality tests, homogeneity tests, and hypothesis tests using t-tests. The results of the study showed that the average value of students' review text writing skills in the experimental class was 85.55, while in the control class it was 79.02. The results of the t-test showed that t count was greater than t table (2.83 > 2.002) at a significance level of 95% with degrees of freedom of 57. Thus, it can be concluded that the Project Based Learning model assisted by local wisdom-based audiovisual media has a significant effect on the review text writing skills of class VIII students of SMP Negeri 3 Batang Anai.